2005
DOI: 10.1093/annonc/mdi019
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of recombinant adenovirus carrying melittin gene on hepatocellular carcinoma

Abstract: Ad-rAFP-Mel can inhibit specifically proliferation of AFP-producing human hepatocarcinoma cells in vitro and in vivo. This suggests that animal toxin gene can be used as an antitumor gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 30 publications
0
26
0
1
Order By: Relevance
“…In a previous study, we have shown that an MMP2 cleavable melittin, the poreforming toxin from honey bee, conjugated with avidin can specifically target tumor cells in vitro and in vivo (20). It has also been shown that recombinant adenovirus encoding a melittin gene controlled by an AFP promoter is effective against hepatocellular carcinoma in vivo (21). In the present study, an MMP2 cleavable fusion gene between LAP and melittin was constructed.…”
Section: Introductionmentioning
confidence: 78%
“…In a previous study, we have shown that an MMP2 cleavable melittin, the poreforming toxin from honey bee, conjugated with avidin can specifically target tumor cells in vitro and in vivo (20). It has also been shown that recombinant adenovirus encoding a melittin gene controlled by an AFP promoter is effective against hepatocellular carcinoma in vivo (21). In the present study, an MMP2 cleavable fusion gene between LAP and melittin was constructed.…”
Section: Introductionmentioning
confidence: 78%
“…To avoid this adverse effect and attempt to achieve a specific killing action on liver cancer, the recombinant adenovirus Ad-rAFP-Mel was constructed with the Mel gene, the α-fetoprotein (AFP) gene and replication-defective adenovirus. Prior results showed that Ad-rAFP-Mel could specifically inhibit proliferation of AFP-producing human hepatocarcinoma cells in vitro and in vivo [6]. The aim of the present study is to observe the effect of Ad-rAFP-Mel on inducing cell apoptosis and interfering with the cell cycle.…”
Section: Introductionmentioning
confidence: 91%
“…The efficiency of adenovirus-mediated gene transferred to BEL-7402 cells was 100% when the multiplicity of infection of Ad-rAFP-Mel was 10 in vitro , and was also high in vivo . The inhibitive rates of recombinant adenovirus Ad-rAFP-MEL for SMMC7721 cells, BEL7402 cells and L-02 cells were about 16.1%, 66.2% and 7.5%, respectively, similarly, the inhibitive rates for recombinant adenovirus Ad-CMV-MEL for the same cells were about 65.9%, 58.9% and 31.7%, respectively whereas a significant antineoplastic effect was observed in vivo by intratumoral injection of Ad-rAFP-MEL [78, 79]. …”
Section: Anticancer Effects Of Bv and Its-conjugatesmentioning
confidence: 99%